﻿Demographic and genetic structure of the quagga mussel, Dreissena rostriformis bugensis, in the Moselle River ten years after first observation - Nicolas Trunfio; Thibaut Bournonville; Nicolas Debortoli; Jonathan Marescaux; Géraldine Nogaro; Jean-Nicolas Beisel (Aquatic Invasions, 2023)
The quagga mussel (Dreissena rostriformis bugensis) was first recorded in France in the Moselle River in 2011. The objective of this study was to obtain a better understanding of the species’ demographic and genetic structure ten years after its first observation. To do this, we examined quagga mussel (i) relative abundance/biomass (compared with the zebra mussel (Dreissena polymorpha), (ii) population structure, and (iii) genetic structure along the navigable stretch of the Moselle during four sampling events conducted between May 2021 and May 2022. The results indicate that, while zebra mussels are still the dominant species (ca. 2/3 of all dreissenid species), quagga mussels represent, on average, 60% of dreissenid biomass. A typical quagga population was composed of five different cohorts with wide, overlapping size ranges, suggesting that the mussels breed for much of the year. Growth in quagga mussel shell length was at least 1.4× greater than that for zebra mussels, regardless of season, with no interruption in growth observed during winter. Unlike zebra mussels, we failed to record any small quagga individuals (4–14 mm shell length) in our samples, possibly indicating high mortality induced by selective predation by invasive round gobies Neogobius melanostomus. Genetically, the three Moselle quagga mussel populations examined were highly homogeneous among themselves (based on microsatellite analysis), and very similar to those found elsewhere in Europe (diversity of CO1 haplotypes). A comparison with previous data suggests that the Moselle quagga population comprises haplotypes introduced over several successive introduction waves, a process that may continue in the future.